FEATURES OF GROWTH PROCESSES OF SCOTS PINE IN PLANTATION AFFECTED BY ANNOSUM ROOT ROT - Dyshko, V. A.; Torosova, L. O. (Forestry and Forest Melioration, 2018)
Introduction Pathogen of the annosum root rot fungus Heterobasidion annosum (Fr.) Bref. acts on a pine tree as a hard factor of natural selection and allows identifying the most resistant genotypes in populations. The mechanisms of this resistance are studied insufficiently; standardized and effective methods for evaluating the resistance of trees are almost absent. At this stage, it is necessary to improve methods for identifying trees with increased resistance to obtain the high-quality seeds. The aim of the study was to investigate the properties of trees with different degrees of resistance to unfavorable factors. Materials and Methods Pine forest stand of V age class affected by annosum root rot was studied. Trees of different health conditions were selected in the die-back foci. The trees growing at a considerable distance from the die-back foci with no external symptoms of the disease were selected as a control. The selection was made based upon the following visual attributes: crown shape, a density of needles location, length and color of the needles. Mensuration parameters (height, diameter, annual height and diameter increment) were determined by common methods According to common methods, mensuration indicators (height, diameter) were measured, increment cores and bast samples for biochemical analysis (protein, proanthocyanidins, catechins) were collected. The productivity of resin formation for trees which significantly different by health conditions was compared. Results We found a diffuse distribution of annosum root rot in the investigated stand. Trees with no visible signs of disease, which were selected to a “disease-resistant” group, have better health condition and dense, bushy crown but significantly (r ? 0,05) differ from the “sick” and “healthy” trees by slower growth in height (havg = 24.5 m). In the disease focus, the trees were more sensitive to changes in climatic factors than specimens selected as a control. By the age of 20, the largest increments were observed for the specimens that at the time of the research were sick, but a clear differentiation in the stand is not traced. During the next period (1995–2015), the trees differentiation in the stand was observed by growth characteristics. The analysis of the annual ring width showed that the percentage of the latewood for the trees with increased resistance was higher than that of diseased trees. The greatest intensity of phenol synthesis, which is associated with the resistance, was observed for the resistant trees. The functional relationship between the main growth characteristics and biochemical compounds are very complex and do not explicitly states the cause-and-effect relations, but only tendencies to it. Sick trees also have low resin productivity. The degree of characteristics variability in tree groups of die-back foci is significantly higher than in healthy trees. Low qualitative variability of parameters for the specific features was observed in diseased trees that may be evidence of inadequacy of response to the impact of the external factors. Creating stands with increased resistance to pathogenic factors today is extremely important. One of the solutions to this problem may be to use high-quality seed material. Therefore, the priority task today is to improve and simplify the methods for evaluating the disease-resistant trees in forest stands and for its use in the selection process.